The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.743546
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin as an Anti-obesity Treatment

Abstract: Obesity is a growing health concern, as it increases risk for heart disease, hypertension, type 2 diabetes, cancer, COVID-19 related hospitalizations and mortality. However, current weight loss therapies are often associated with psychiatric or cardiovascular side effects or poor tolerability that limit their long-term use. The hypothalamic neuropeptide, oxytocin (OT), mediates a wide range of physiologic actions, which include reproductive behavior, formation of prosocial behaviors and control of body weight.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 313 publications
(821 reference statements)
1
16
1
1
Order By: Relevance
“…Previous studies suggest that OXT may have anti-depressant, anxiolytic and appetite suppressing effects [12][13][14][15][16]42]. Also, available data suggest that rs2254298 G/ A and rs53576 A/A alleles may be related with neuroticism and various psychopathologies [12][13][14][15][16]. Partially supporting those results, we found that OXT levels were signi cantly reduced among obese youth while rs53576 G/ G allele was signi cantly elevated and rs2254298 allele displayed no signi cant difference.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies suggest that OXT may have anti-depressant, anxiolytic and appetite suppressing effects [12][13][14][15][16]42]. Also, available data suggest that rs2254298 G/ A and rs53576 A/A alleles may be related with neuroticism and various psychopathologies [12][13][14][15][16]. Partially supporting those results, we found that OXT levels were signi cantly reduced among obese youth while rs53576 G/ G allele was signi cantly elevated and rs2254298 allele displayed no signi cant difference.…”
Section: Discussionsupporting
confidence: 86%
“…The rs53576 and rs2254298 polymorphisms in oxytocin receptor may be especially important in this regard [14]. Previous studies suggest that OXT may have anti-depressant, anxiolytic and appetite suppressing effects [12][13][14][15][16]42]. Also, available data suggest that rs2254298 G/ A and rs53576 A/A alleles may be related with neuroticism and various psychopathologies [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, a hybrid intervention with OXT and psychotherapy has been shown to have a potent effect on PTSD severity ( Flanagan et al, 2018 ), though these effects reportedly vary across the sexes ( Frijling et al, 2015 ). Likewise, OXT, being anorectic, functions as a “nutrient status sensor” ( McCormack et al, 2020 , p. 122), and is found to reduce obesity across humans, rodents, and non-human primates ( Niu et al, 2021 ), through its effect on consumptive behaviors by simultaneously regulating cognitive control as well as food reward processing ( Spetter et al, 2018 ). Importantly, increased OXT signaling and secretion are known to regulate both energy intake and energy expenditure which result in weight loss by its effect on fat mass loss (as opposed to lean mass loss) ( McCormack et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%